THE USE OF ADVENTURE BOOKS IN FOSTERING CHILDREN’S LANGUAGE SKILL - Harry, Steffany Cleryica; Hassan, Hariany Mohd; Elian, Aisyah Bin; Valintine, Mary Gorrete Bte; Idek, Sirhajwan (PEOPLE: International Journal of Social Sciences, 2019)
The goal of this study was to investigate the role of an adapted and modified version of Busy Book known as “Adventure Book” in fostering children’s language skills. With the rise of technology, books seem to become less significant as mobile devices become increasingly more integral to our everyday life and education. Thus, this study aimed to highlight the role and importance of books as an essential material in learning especially for children aged 3 to 4-year-old. The Adventure Book is a type of book that provides tactile experience to children as it was adapted from ‘Busy Book’, a popular type of children’s books. The book contained simple and basic English language as well as easy-to-read stories with moral values and familiar characters. The book contained simple activities that could help children develop their cognitive skills. The study was conducted on 30 children of 3 to 4-year-old at local nurseries and it involved their parents and teachers. The instrument used in this study was questionnaire. The findings indicated positive responses from the children and the guardians on the application of the books.